Sedimentary infill of shallow water deltaic sand bodies controlled by small-scale syndepositional faults related paleogeomorphology: Insights from the paleogene Shahejie formation in the Dongying depression, Bohai Bay Basin, Eastern China. (August 2020) - Dou, Luxing; Hou, Jiagen; Liu, Yuming; Zhang, Li; Song, Suihong; Wang, Xixin
Abstract: Formed in extensional structural system, syndepositional faults are widely distributed in rift basins. Large basinal scale syndepositional faults play important roles in controlling the development and dispersion of depositional systems in rift basins. When it comes to the intensively developed small-scale syndepositional faults related to those large basinal scale syndepositional faults in complex fault blocks, the controlling effects to sedimentary architecture in the finer scale are still not well understood in the depositional systems. Thus, commonly used sedimentary models without considering small-scale syndepositional faults related paleogeomorphology are difficult to apply in complex fault blocks of rift basins. In this study, using the interpretation of 3D seismic profiles, wire-line log curves, and cores, patterns of small-scale syndepositional faults and their related finer scale stratigraphic sequences are described in the upper Es2 member, Shahejie Formation of the W43 complex fault block area, Dongying Depression, Bohai Bay Basin. The syndepositional faults are intensively distributed in the W43 complex fault block area. Based on the interpretation of sequence boundaries, four types of syndepositional faults related paleogeomorphology units were identified. They are named the micro slope break belt, micro-horst belt, and the micro-graben belt. The stacking patterns and development scale of individual deltaic sand bodies in the parasequences are controlled by activity of the syndepositional faults. In the hanging wall area near the syndepositional fault of the micro-step and micro-graben, thickened multi-stage continuously individual sand bodies are deposited controlled by low topography during the depositional period with sufficient sediment supply. In the footwall area of single micro syndepositional fault and micro-horst belt, individual sand bodies became thinner and less aggraded in vertical direction. The small-scale syndepositional fault-related paleogeomorphology is a new important factor that controls the sedimentary architecture of the shallow water deltaic sand bodies in the rift basin. This study provides insights into tectonic control of finer-scale sedimentary architecture and hydrocarbon reservoirs development in continental rift basins. Highlights: Small-scale syndepositional faults in typical complex fault block of a rift lacustrine basin. Small-scale syndepositional normal faults related paleogeomorphology. Infill of deltaic reservoirs influenced by the small-scale syndepositional faults related paleogeomorphology.